Competitive Analysis of Online Grocery Markets in the Baltic States - Kovacova, Irina (2024)
The aim of this thesis is to offer a comprehensive analysis of the online grocery market in the Baltic States using competitive intelligence practices and tools. The thesis applies the theoretical frameworks of competitive intelligence to analyse basic market dimensions such as market size, market shares, trends and competition. It examines the e-commerce landscape across different periods, including pre-COVID, COVID, and post-COVID eras, and compares the Baltic States' e-commerce development to other regions. The research includes detailed insights into the largest online grocery market players, Barbora and Rimi Baltic, and uses Porter’s Five Forces framework to evaluate industry dynamics. Additionally, it explores differences in logistics, payment options, loyalty programs and website performance between the key players. The study seeks to provide valuable insights for current industry players and newcomers, enhancing comprehension of the evolving online grocery market in the Baltic States.